Early Performance of Recently Released Rootstocks with Grapefruit, Navel Orange, and Mandarin Scions under Endemic Huanglongbing Conditions in Florida - J. Martin Zapien-Macias; Rhuanito Soranz Ferrarezi; Peter D. Spyke; William S. Castle; Frederick G. Gmitter; Jude W. Grosser; Lorenzo Rossi (Horticulturae, 2022)
Huanglongbing (HLB), which is believed to be caused by the phloem-restricted bacterium Candidatus Liberibacter asiaticus (CLas), has decimated Florida’s citrus production. Grapefruit production has declined 75%, mandarin 78%, and sweet orange 52% due to the high sensitivity of commercial scions and rootstocks to the disease. New combinations of scions and hybrid rootstocks may provide better performance than current commercial selections for Florida’s fresh citrus production, particularly in the Indian River District. The objective of this study was to evaluate and compare University of Florida rootstocks and other recently released rootstocks grafted with grapefruit, navel orange, and mandarin scions by measuring tree growth and HLB tolerance. Three independent large-scale field trials were established in September 2019 in Fort Pierce, FL, USA. Trial 1 (T1) included 36 rootstocks with ‘Ray Ruby’ grapefruit as the scion; Trials 2 and 3 (T2 and T3, respectively) included 30 rootstocks with ‘Glenn’ navel orange F-56-11 and ‘UF-950’ mandarin as the scion, respectively. Tree canopy volume, trunk diameter, CLas titer, HLB severity index, and leaf nutrient concentrations were evaluated during 2020 and 2021. Significant differences among rootstock-scion combinations were found in each trial for most of the assessed traits. In T2, UFR-15 consistently developed the largest ‘Ray Ruby’ grapefruit trees during both years. In T3, ‘Glenn’ navel orange F-56-11 trees were larger on C-22, and US-802. Similarly, US-802 and US-942 generated the largest ‘UF-950’ mandarin trees. Overall, trees had optimum levels of macro- and micronutrients except for calcium. CLas infection and HLB visual index varied among scion-rootstock combinations, especially during the first year of growth when intensive flushing was produced. Generally, trees grew vigorously with WGFT+50-7 and Willits inducing the lowest HLB symptoms in all evaluations. Production and fruit quality need to be evaluated to determine the suitability of potential scion-rootstock combinations that can confer consistent economical and biological advantages under the current HLB scenario in the Indian River District.